The Technical Efficiency of African Countries: A DEA Methodology - Thabang Ndlovu (Review of Socio-Economic Research and Development Studies, 2025)
The primary objective of this study is to investigate the economic efficiency performance of African nations. Economic efficiency plays a crucial role in the economic growth of nations. By employing resources in a more efficient manner, nations are able to produce more output with the same or less inputs, which contributes to more sustainable economic growth. In assessing the economic efficiency of Africa nations, this study first employed Data Envelopment Analysis methodology in order to estimate the technical efficiency, scale efficiency and pure technical efficiency of the aforementioned countries for the period 1990 to 2023. The empirical results revealed that, with regard to the African context, there is scope for African countries to improve their efficiency by adopting new and innovative technology to produce more output more efficiently in their respective economies. Second, this study estimated the Malmquist Productivity Indexes, efficiency changes, and technology changes for a select list of African countries in order to assess the productivity changes of the aforementioned countries. Empirical results revealed, on average, a slight increase in productivity for African countries during the period 1990 to 2023. Lastly, this study evaluated the rate of efficiency convergence in a list of selected African countries during the period 1990 to 2023. The empirical results revealed that inefficient African countries were able to catch up with more efficient countries during the period assessed.